Hemostasis biomarkers in multiple sclerosis. (26th June 2018) - Ziliotto, N.; Bernardi, F.; Jakimovski, D.; Baroni, M.; Marchetti, G.; Bergsland, N.; Ramasamy, D. P.; Weinstock‐Guttman, B.; Schweser, F.; Zamboni, P.; Ramanathan, M.; Zivadinov, R.
Abstract : Background and purpose: The aim was to investigate the plasma levels of hemostasis components in multiple sclerosis (MS) and their association with clinical and magnetic resonance imaging (MRI) outcomes. Methods: In all, 138 MS patients [85 with relapsing–remitting MS (RR‐MS) and 53 with progressive MS (P‐MS) with a mean age of 54 years; 72.5% female; median Expanded Disability Status Scale 3.5; mean disease duration 21 years] and 42 age‐ and sex‐matched healthy individuals (HI) were studied. All subjects were examined with 3 T MRI and clinical examinations. Plasma levels of hemostasis factors [procoagulant, factor XII (FXII)] and inhibitors [tissue factor pathway inhibitor (TFPI), thrombomodulin, heparin cofactor II, a disintegrin‐like and metalloprotease with thrombospondin type 1 motif 13 (ADAMTS13) and plasminogen activator inhibitor 1 (PAI‐1)] were evaluated by magnetic Luminex assays and enzyme‐linked immunosorbent assay. Associations between hemostasis plasma levels and clinical and MRI outcomes were assessed. Results: Lower ADAMTS13 levels were found in MS patients compared to HI ( P = 0.008) and in MS patients presenting with cerebral microbleeds compared to those without ( P = 0.034). Higher PAI‐1 levels were found in MS patients compared to HI ( P = 0.02). TFPI levels were higher in the P‐MS subgroup compared to RR‐MS patients ( P = 0.011) and compared to HI ( P = 0.002). No significant associations between hemostasis plasma levels and clinical or MRI outcomes were found. Conclusions: Decreased ADAMTS13, particularly in MS patients with cerebral microbleeds, which deserves further investigation, and increased PAI‐1 and TFPI levels were observed in MS patients, which deserves further investigation. No relationship between hemostasis plasma levels and measures of disease severity was detected.